Application of User Generated Content by Television News’ during Pandemic - Rahmatul Furqan; Sitti Murniati Muhtar; Nasakros Arya (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2022)
The revolution of technology has always shaped the works of journalism, including the news content and its relationship with the public. Along with the digital era, people started to participate in and contribute to journalism. User Generated Content (UGC) has regularly altered both information flows and the nature of news work for the mainstream media. By conducting a qualitative content analysis, this study tries to examine the use of UGC by 24-hour news TV channels in Indonesia in relation to the context of participatory journalism in the Covid-19 pandemic situation. The results of this study indicate that four 24-hour TV news channels in Indonesia are beginning to negotiate most of their ‘professional logic’ towards the logic of ‘adaptation’. Overall, framing analysis shows that news TV stations’ use of UGC has not optimally encouraged more constructive pandemic journalism practices.